World report 2016 - Watch, Human Rights (Bristol University Press, 2023)
The human rights records of more than 90 countries and territories is put into perspective in Human Rights Watch’s signature yearly report. This volume highlights the armed conflict in Syria, international drug reform, drones and electronic mass surveillance, and also features photo essays of child marriage in South Sudan, the cost of the Sochi Winter Olympics in Russia, and religious fighting in Central African Republic. Reflecting extensive investigative work undertaken in 2015 by Human Rights Watch staff, in close partnership with domestic human rights activists, the annual World Report 2016 is an invaluable resource for journalists, researchers, students, diplomats, and citizens, and is a must-read for anyone interested in the fight to protect human rights in every corner of the globe.The human rights records of more than 90 countries and territories is put into perspective in Human Rights Watch’s signature yearly report. This volume highlights the armed conflict in Syria, international drug reform, drones and electronic mass surveillance, and also features photo essays of child marriage in South Sudan, the cost of the Sochi Winter Olympics in Russia, and religious fighting in Central African Republic. Reflecting extensive investigative work undertaken in 2015 by Human Rights Watch staff, in close partnership with domestic human rights activists, the annual World Report 2016 is an invaluable resource for journalists, researchers, students, diplomats, and citizens, and is a must-read for anyone interested in the fight to protect human rights in every corner of the globe.